2020
DOI: 10.11591/ijere.v9i2.20454
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality assessment of binary response test items: A non-parametric approach of bayesian item response theory measurement

Abstract: This study investigated dimensionality of Binary Response Items through a non-parametric technique of Item Response Theory measurement framework. The study used causal comparative research type of non-experimental design. The sample consisted of 5,076 public senior secondary school examinees (SSS3) between the age of 14-16 years from 45 schools, which were drawn randomly from three senatorial districts of Osun State, Nigeria. Instrument used for this study was 2018 Osun State unified multiple-choice mathematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…For instance, the National Benchmark Test in South Africa consists of Academic Literacy, Quantitative Literacy, and Mathematics; Graduate Management Admission Test consists of mathematics, verbal reasoning, quantitative reasoning, and English language; Joint Admission and Matriculation Board consist of Mathematics, English, Physics, Chemistry, Biology and so on. Also, this result laid credence to the findings of [5,6], which argued that there was no evidence of unidimensionality in 2018 Osun State unified multiple-choice mathematics achievement test items. However, this result was in dissonance with the findings of [4,48] that the unidimensionality of the test was met when comparing three methods for evaluating dimensionality.…”
Section: Discussionsupporting
confidence: 70%
“…For instance, the National Benchmark Test in South Africa consists of Academic Literacy, Quantitative Literacy, and Mathematics; Graduate Management Admission Test consists of mathematics, verbal reasoning, quantitative reasoning, and English language; Joint Admission and Matriculation Board consist of Mathematics, English, Physics, Chemistry, Biology and so on. Also, this result laid credence to the findings of [5,6], which argued that there was no evidence of unidimensionality in 2018 Osun State unified multiple-choice mathematics achievement test items. However, this result was in dissonance with the findings of [4,48] that the unidimensionality of the test was met when comparing three methods for evaluating dimensionality.…”
Section: Discussionsupporting
confidence: 70%
“…Uni-dimensionality is a key feature of measurement theory that can be used to evaluate variable interrelationships. When the eigenvalue of the first value has higher percentage over the next one, uni-dimensionality is usually supported [37], [42]. The finding revealed that EDU222 achievement test sufficiently meets the assumption of unidimensionality, as determined by [33] using factor analysis with the eigenvalues-greater-than-one rule.…”
mentioning
confidence: 83%
“…This evaluation activity is generally carried out conventionally (Barua, Singh, Mridiula, Gupta, Satyapriya & Tomar, 2017;Hardianti,Taufiq & Pamelasari, 2017;Abdurrahman, Saregar & Umam, 2018;Ozan, 2019;Violato & King, 2021). However, with the development of technology, evaluation can be integrated with technology (Sakar, Orhan, Sinanoğlu, Tosun & Öz, 2017;Ayanwale, Isaac-Oloniyo & Abayomi, 2020;Esomonu, Esomonu & Eleje, 2020). So it is necessary to develop a technology-based assessment system to facilitate the assessment process.…”
Section: Introductionmentioning
confidence: 99%